James Cahill, C.C. Wang, Lynn King. C.C. Wang: Landscape Paintings. Hong Kong, Hsi An T’ang, distribuido por University of Washington Press, Seattle, 1986. 91 pp. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1988)
-